Improvement of corrosion resistance of aluminium coatings at electric-arc sputtering with pulsating spraying flow - Kriuchkov, N. S.; Royanov, V.A.; Zakharova, I.V. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Annotation: spraying technology is widely used to restore and strengthen worn parts of equipment in machine-building, metallurgical, mining, agricultural industries, which operate in abrasive, shock-abrasive, and gas-abrasive wear conditions and to which new and more stringent requirements are constantly applied. Due to the increasing requirements for the quality and operational resistance of the restored surfaces of parts, the issues of improving the quality of coatings are very relevant for enterprises of various industries. The major disadvantage of arc spraying is the process of oxidation of metal droplets during transportation to the processed surface, which has a significant impact on the quality of the coating and its operational characteristics.